2014
DOI: 10.1063/1.4873522
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectrically induced mechano-catalytic effect for degradation of dye wastewater through vibrating Pb(Zr0.52Ti0.48)O3 fibers

Abstract: Electric field modulation of magnetism and electric properties inLa-Ca-MnO3/Pb(Zr0.52Ti0.48)O3 magnetoelectric laminate J. Appl. Phys. 113, 17C712 (2013); 10.1063/1.4795871 Stress-controlled Pb(Zr0.52Ti0.48)O3 thick films by thermal expansion mismatch between substrate and Pb(Zr0.52Ti0.48)O3 filmHydrothermally synthesized piezoelectric Pb(Zr 0.52 Ti 0.48 )O 3 fibers were used as a mechano-catalyzer to degrade acid orange 7 dye wastewater via the mechano-catalytic effect, which was achieved as a product of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(90 citation statements)
references
References 24 publications
0
90
0
Order By: Relevance
“…Some traditional piezoelectric materials, such as BaTiO 3 and SrTiO 3 , exhibited excellent piezocatalytic activity for degrading methyl orange or producing H 2 O 2 under ultrasonic vibration . Lin et al illustrated the high piezocatalytic activity of Pb(Zr 0.52 Ti 0.48 )O 3 (PZT) fibers for acid orange 7 degradation subjected to an external mechanical vibration . In addition to traditional piezoelectrics, our group has revealed that the macroscopic polarization enhancement derived from vanadium doping endowed the pyroelectric BiOIO 3 superior piezocatalytic performance in the evolution of •O 2 − and •OH under ultrasonic irradiation; meanwhile, its photocatalytic •O 2 − and •OH production activities were also promoted .…”
Section: Introductionmentioning
confidence: 88%
“…Some traditional piezoelectric materials, such as BaTiO 3 and SrTiO 3 , exhibited excellent piezocatalytic activity for degrading methyl orange or producing H 2 O 2 under ultrasonic vibration . Lin et al illustrated the high piezocatalytic activity of Pb(Zr 0.52 Ti 0.48 )O 3 (PZT) fibers for acid orange 7 degradation subjected to an external mechanical vibration . In addition to traditional piezoelectrics, our group has revealed that the macroscopic polarization enhancement derived from vanadium doping endowed the pyroelectric BiOIO 3 superior piezocatalytic performance in the evolution of •O 2 − and •OH under ultrasonic irradiation; meanwhile, its photocatalytic •O 2 − and •OH production activities were also promoted .…”
Section: Introductionmentioning
confidence: 88%
“…[9] In at ypical piezo-catalytic process, piezoelectric materials generate an electric field with external mechanical force, which can drive charge carriers (electrons and holes) participating in redox reactions such as water splitting [7,10] or elimination of pollutants. [9,11,12] Mechanistic analysis showedt hat H 2 O 2 could be generated in situ in the electrochemical process. [13] However,i n the process of pollutant degradation through the piezo-catalytic effect, H 2 O 2 is overlooked or only regarded as one of the active species to remove the pollutantsa nd the mechanism of generating H 2 O 2 is unclear.…”
mentioning
confidence: 99%
“…In pyro-electric material, the spontaneous polarization (Ps) dipole moment is non-zero, which results in the existence of bound polarization charges in the two opposite sides of the inner surface. When the temperature comes to a constant, the bound polarization charges are shielded by these equal and opposite absorbed charges on the surface of pyro-electric material; the result is electrically neutral [30]. When pyro-electric material is heated, the Ps density decreases as dipole The principle of pyro-electro-chemical catalysis can be described as in Figure 5: With temperature gradient (∆T), pyro-electric materials have the ability to achieve thermal-to-electric conversion.…”
Section: Resultsmentioning
confidence: 99%